2014
DOI: 10.1002/mrd.22427
|View full text |Cite
|
Sign up to set email alerts
|

Mating decreases plasma levels of TGFβ1 and regulates myosalpinx expression of TGFβ1/TGFBR3 in the rat

Abstract: Mating shuts down a 2-methoxyestradiol (2ME)-dependent, non-genomic activity that is responsible for accelerating egg transport in the rat oviduct. The aims of this work were to investigate the role of TGFβ1 in this 2ME-reduced activity and to determine the effect of mating on the expression and distribution of TGFβ1 and its receptor TGFBR3 in the rat oviduct. We determined the level of TGFβ1 in the plasma and oviductal fluid at 1, 3, or 6 hr during Day 1 of the oestrous cycle in unmated or mated animals. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Oróstica et al () showed that mating increases TNFα abundance in the oviduct fluid, and that administering this cytokine into the oviduct of cycling rats mimicked the effect of mating, accelerating E 2 ‐induced egg transport. Mating decreased TGFβ1 concentration in the plasma but not the oviduct fluid; however, neutralization of circulating TGFβ1 did not prevent the effect of E 2 on egg transport (Oróstica et al, ). Taken together, these results indicate that TNFα is a mating‐induced signal that can switch how E 2 accelerates oviductal egg transport from a non‐genomic to a genomic pathway.…”
Section: Mating Inhibits the Non‐genomic E2 Pathway In The Oviduct Thmentioning
confidence: 99%
“…Oróstica et al () showed that mating increases TNFα abundance in the oviduct fluid, and that administering this cytokine into the oviduct of cycling rats mimicked the effect of mating, accelerating E 2 ‐induced egg transport. Mating decreased TGFβ1 concentration in the plasma but not the oviduct fluid; however, neutralization of circulating TGFβ1 did not prevent the effect of E 2 on egg transport (Oróstica et al, ). Taken together, these results indicate that TNFα is a mating‐induced signal that can switch how E 2 accelerates oviductal egg transport from a non‐genomic to a genomic pathway.…”
Section: Mating Inhibits the Non‐genomic E2 Pathway In The Oviduct Thmentioning
confidence: 99%